QUALITATIVE EVALUATION OF MORAL DILEMMA DISCUSSION PROGRAM FOR UNDERGRADUATE MEDICAL STUDENTS - Pratomo, Fransiskus Aryo; Rahayu, Gandes Retno; Suhoyo, Yoyo (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2023)
Background: In order to achieve professionalism in the medical profession, competence in medical knowledge and skills is crucial. However, equally important are affective components that encompass moral values. At Widya Mandala University Medical School, moral dilemma discussions are employed as a method to enhance the ethical and moral development of students. To optimize the impact of this method on students, it is necessary to delve deeper into the processes that occur within it. This study aims to qualitatively evaluate the student experience of moral dilemma discussions in terms of their moral development and ethical reasoning, their perception of the method as a learning tool, and their assessment of its effects on their moral development and ethical reasoning.Methods: This study utilized a qualitative phenomenological approach to assess the student experience of moral dilemma discussions. In-depth interviews were conducted with 15 student participants from three different academic years. The data obtained were qualitatively analyzed using the thematic analysis method.Results: The in-depth interviews with the 15 study participants yielded four main themes, namely moral development, self-development, the process of assimilation and accommodation, and enabling factors.Conclusion: All students who took part in the study reported a self-perception of higher stage of moral development. According to their experiences, moral development occurred through a process involving ethical contextualization, exposure to various points of view, and reflection. Important factors to consider include sufficient preparation, an active and enjoyable atmosphere, the use of relevant cases, and a longitudinal process.